ENVIRONMENTALLY BASED TOURISM IN THE TRANSFORMATION OF THE REGIONAL ECONOMIC STRUCTURE OF EAST JAVA WITH LOCATION QUOTIENT AND SPATIAL PANEL ANALYSIS - Renta Yustie; Ermatry Hariani; Betty Silfia Ayu Utami; Novi Theresia Kiak (PT. Habe Cendekia Utama, 2026)
The transformation of the regional economic structure in East Java is influenced by the development of environmentally based tourism, along with the increasing demands for sustainable development and inter-regional ecological conditions. While the tourism sector is seen as a driver of regional economic growth, empirical evidence linking sectoral specialization, environmental quality, and spatial linkages within a regional economic framework is still limited. This study aims to analyze the role of environmentally based tourism in driving the transformation of the regional economic structure in East Java. The study uses panel data from regencies and cities in East Java over several years of observation 2015 until 2024. Location Quotient is applied to identify the comparative advantages of the tourism sector, while a spatial panel regression model is used to estimate the influence of tourism and environmental variables on regional economic performance, taking into account spatial dependencies between regions. The analysis results indicate that environmentally based tourism has a high level of specialization in several regions and contributes positively and significantly to regional economic growth. Empirical findings also reveal spatial spillover effects, where tourism development in a region influences the economic performance of surrounding regions, with the environment acting as a moderating factor. This study offers novelty by integrating the Location Quotient and spatial panel econometrics in the study of environmentally based tourism and provides important policy implications for sustainable regional economic development planning.